Usability of SIPAHAJI: An Information and Communication System Innovation to Support Jakarta Smart City - Priono, Mochamad; Sufandi, Unggul Utan; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Anam, Khaerul (ISB Atma Luhur, 2024)
This research addresses the problem of insufficient information and communication systems for halal tourism in Jakarta, which affects both tourists and local stakeholders. The study aims to evaluate the Android-based SIPAHAJI application, designed to support the Smart City concept by providing tourists with efficient and effective information about halal tourism destinations in Jakarta. The app employs collaborative filtering and location-based filtering to offer personalized recommendations based on user preferences and location. The methodology includes black box testing to assess the app's functionality and User Acceptance Testing (UAT) to evaluate user satisfaction. Respondents, consisting of experts and public stakeholders with professional experience or education in the tourism industry, were selected through quota sampling. Questionnaires were used for data collection. The results indicate that the application functions effectively, demonstrating excellent usability and high user acceptance. Respondents reported satisfaction with the app’s easy-to-use interface, which enhances the overall travel experience. Additionally, the app has the potential to optimize the Smart City concept, helping tourists navigate halal attractions and potentially increasing tourist visits, which could positively impact the local economy in alignment with the Sustainable Development Goals (SDGs).